EFFECT OF ACUTE AND CHRONIC DOSING OF SOME PARTS OF PAPAYA TREE ON ESR LEVELS SUGGESTING ITS ANTI-INFLAMMATORY POTENTIAL - Muhammad Osama; Rahila Ikram; Calvin R. Wei; Raheela Saleem; Geeta Kumari; Fahad Jibran Siyal; Soha Khan; Shoaib Alam (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
A big portion of world’s population consumes natural substances to deal with unhealthy conditions. Carica Papaya L. of Caricaceae family is a herbaceous plant. Various parts of this plant including fruits, leaves, roots, peel, seeds have different distinctive therapeutic value. Papaya fruit has laxative properties, seeds have anti-tumor effect, whereas papaya leaves have become recognized for their beneficial effects on bowel movement. This study was conducted to observe and investigate the effect of short-term and long-term dosing of different edible (ripe and unripe fruit) and non-edible (seeds and leaves) parts of papaya on erythrocyte sedimentation rate (ESR) in rabbits. Acute and chronic dosing of all types of papaya extract showed no significant effect on ESR. Chronic dosing of Ripe Papaya fruit solution significantly lowered the serum ESR. No significant difference was found between the acute and chronic dosing days of each group. It was concluded that chronic dosing of Carica papaya Linn. extracts, including the fruit, seed, and leaf, may possess anti-inflammatory properties as evidenced by reduction in ESR values. However, future in-vivo and in-vitro studies are recommended to confirm anti-inflammatory effect and its exact mechanism